Development of LabVIEW-based multilevel inverter with reduced number of switches. (1st January 2014) - Kirubakaran, A.; Vijayakumar, D.
In the present scenario, the development of multilevel inverter is becoming popular for industrial applications and higher scale renewable green power technologies such as fuel cell, PV cell and wind turbine systems connected to the load. But the traditional multilevel topologies have large components and complex Pulse Width Modulation (PWM) controller leading to reduced harmonics and voltage stress on the load. Therefore, a new topology of a cascaded multilevel inverter employing less number of switches with reduced gate driver circuits and simple control scheme is presented in this paper. A comprehensive MATLAB/Simulink model of a seven-level inverter and the generation of control pulses using multi-carrier-based PWM is evolved and discussed. With the aid of LabVIEW, an experimental prototype is developed and their results are compared with simulation results.